Feed a child wisdom and he will eat wisely for life - New Straits Times, (2012)
AFTER just one year, the children involved in the Nestle Healthy Kids (NHK) Intervention Study are already showing encouraging results in their eating habits, empowered by their newfound knowledge of nutrition.